Natural Pesticides in Indian Agriculture Sector: A Minireview - Sarkar, S.; Sultana, S.; Hembram, S.; Saha, S.; Ganguly, B.; Barman, P.; Pal, P. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This systematic study explored the process of formulation, preparation and application of natural pesticide molecules in Indian agriculture with a focus on leveraging such pest management strategies instead of synthetic pesticides as cleaner alternatives. Natural pesticides developed from herbs and essential oils have been considered as environmentally safe options with target specificity due to increasing awareness about environmental health and insect resistance. It presents a review of classical and recent developments in formulation methods, their production techniques and regulatory system followed for natural pesticides along with an overview of the advantages and disadvantages of these pesticides in Indian agriculture. The review addresses some of the practical challenges, like scalabilty, economic feasibility and effectiveness across a range of irrigated crops and pest species. The small proportion of studies that evaluated natural pesticides mainly identified them as contributing towards sustainability, but there is little information on their effectiveness or cost–benefit potential compared to synthetic pesticides, highlighting the need for further research. Investing in more rapid need-based optimizations of formulation steps, enhancing access to market and other policies enabling natural pesticide promotion at work will soon be looked into place natural pesticides in Indian cropping systems.